Perm Research Institute of Agriculture is 110 years old. The past and the present - K. N. Korlyakov; I. P. Ogorodov (Аграрная наука Евро-Северо-Востока)
Perm Research Institute of Agriculture is the legal successor of the Perm Provincial Experimental Station, founded in 1913. The article presents a brief outline of the Institute history, as well as the overview of the Institute research for the period since 1913 to the present. The main direction of the Experimental Station work, later the Institute, was the cultivation of poor sod-podzolic soils of the Urals. The bases of scientific research are long-term stationary experiments included to Russian Geographical Network of experiments with fertilizers. At present, the institute is moving to complex interdisciplinary research aimed at developing regenerative farming systems, developing a new direction in fodder production – the use of biologically active feeds, application of precision farming technique, the development of new technologies using methods and means of agrobiophotonics to increase the productivity of crops, monitoring and control of pathogens and pests, strengthening the environmental aspect in research.